2022
DOI: 10.1155/2022/5096825
|View full text |Cite
|
Sign up to set email alerts
|

Potential Protective Effects of Antioxidants against Cyclophosphamide-Induced Nephrotoxicity

Abstract: Cyclophosphamide is an alkylating antineoplastic agent, and it is one of the most successful drugs with wide arrays of clinical activity. It has been in use for several types of cancer treatments and as an immunosuppressive agent for the management of autoimmune and immune-mediated diseases. Nowadays, its clinical use is limited due to various toxicities, including nephrotoxicity. Even though the mechanisms are not well understood, cyclophosphamide-induced nephrotoxicity is reported to be mediated through oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 92 publications
0
18
0
2
Order By: Relevance
“…These outcomes are consistent with the nephrotoxicity observed in the renal tissues of rats treated with CP in the current study. Several natural and other antioxidants are beneficial and effective source for preventing renal damage [27]. Previous studies have revealed the beneficial potential of βglucan, a natural product on kidney [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes are consistent with the nephrotoxicity observed in the renal tissues of rats treated with CP in the current study. Several natural and other antioxidants are beneficial and effective source for preventing renal damage [27]. Previous studies have revealed the beneficial potential of βglucan, a natural product on kidney [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…If it is necessary to use drugs with significant potential nephrotoxicity, detailed recommendations are developed to prevent their harmful effects on the kidneys. For example, reference can be made to the prophylactic use of antioxidant compounds (vitamin E, vitamin C, flavonoids, melatonin, N-acetylcysteine, luteolin, lycopene, or coenzyme Q10) that reduce free radical damage in the course of the use of drugs that increase oxidative stress in kidney tissues, e.g., during treatment with vancomycin [ 101 ], cyclophosphamide [ 102 ], colistin [ 103 ], cyclosporine A [ 104 ], tacrolimus [ 105 ], contrast media [ 106 ], and cisplatin [ 107 ]. Antioxidants, vitamins, and minerals were also demonstrated to prevent gentamicin-induced nephrotoxicity [ 108 ].…”
Section: Preventive Factors Of Drug-induced Nephrotoxicitymentioning
confidence: 99%
“…7 Preclinical evidence also emphasizes the increased apoptosis where increased caspases, cytochrome C, dysfunctional mitochondria, and calcium overload were found. 4,5,7,8 In addition to increased oxidative stress, inflammation, and apoptosis, CPM administration is also reported to cause renal fibrosis and increased levels of transforming growth factor beta 1 (TGF-β1). 6 Hence, a multifactorial approach exists for the management of CPM-induced nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%